(untitled) (Innovative professional education, 2022)
The main difficulties of information perception and its implementation by future PhD in the flield of 015 «Vocational (Professional Education)» in creating a structure and filling a virtual institution of professional education according to the discipline program «Methodology of creating electronic educational resources in professional education» have been analyzed. The advantage of virtual educational institutions of professional education is determined as an opportunity for students to organize virtual exchange projects – online interpersonal events that contribute to intercultural dialogue and the development of non-technical skills.